Sodium ion positive electrode material and preparation method thereof, and sodium ion battery positive electrode

By coating phosphonic acid molecules on the surface of layered oxide materials of sodium ion batteries, the problems of degradation of instability and electrochemical performance in the air are solved, and the high stability and low cost production of the materials are achieved, which is suitable for industrial applications. .

CN119275272APending Publication Date: 2025-01-07GREATER BAY AREA INST FOR INNOVATION HUNAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411439890.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The layered metal oxide positive electrode material of sodium ion battery is unstable in the air and is prone to chemical reactions with moisture and carbon dioxide, affecting its structural stability and electrochemical properties, and increasing production costs.

Method used

The surface of sodium ion layered oxide material is coated with nanoscale by using phosphonic acid self-assembly single-molecule layer, and through the strengthened bond connection between phosphonic acid molecules and the hydroxyl group on the surface of the oxide material, an orderly single-molecule layer is formed to prevent water. Direct contact between molecules and the surface layer of the material inhibits chemical reactions.

Benefits of technology

It significantly improves the chemical stability and electrochemical properties of layered oxide materials, reduces production costs, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275272A_ABST
    Figure CN119275272A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ion positive electrode material and a preparation method thereof. The sodium ion positive electrode material comprises a layered oxide NaxMyNzTiON and phosphonic acid molecules coating the surface of the layered oxide, the mass of the phosphonic acid molecules accounts for 1-5% of the mass of the layered oxide matrix Na < x > M < y > N < z > TiON; wherein M, N and T are different types of metal elements and are selected from one or more of Ni, Fe, Mn, Li, Ca, Al, Mg, Zr, Nb, Ta, Ti, Sn, Co and Cu; 0.66 < = x < 1.1, 0 < = y < = 1, 0 < = z < = 1, 0 < = i < = 1, y + z + i = 1, 1.85 lt; nlt; 2.15, 2.15; the values of x, y, z, i and n meet the charge balance of the chemical formula. According to the sodium ion positive electrode material, the chemical stability of a layered oxide material in ambient air can be remarkably improved, so that the electrochemical performance of the sodium ion positive electrode material is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a sodium ion positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] As energy demand grows and environmental awareness increases, it becomes crucial to develop battery materials with high energy density and excellent cycle performance. Currently, lithium-ion batteries are widely used due to their high energy density and good cycle performance. However, the scarcity of lithium resources leads to high costs, and the uneven distribution of resources and difficulty in mining increase production costs. In addition, lithium batteries have safety hazards, such as overheating that may cause fire or explosion. Sodium-ion batteries are seen as a promising alternative technology because of their abundant raw materials, low cost and environmental friendliness. Sodium resources are widely distributed and easy to extract, giving sodium-ion batteries advantages in cost and supply chain sustainability, helping to reduce battery production costs and improve environmental adaptability and safety.

[0003] Sodium-ion batteries, especially their layered oxide cathode materials, have attracted attention due to their many advantages. The basic structure of this material consists of octahedral units composed of transition metals and oxygen, forming transition metal layers, and sodium ions migrate between these layers. The high energy density, high capacity, stable cycle performance and fast ion transport capabilities of layered oxide cathodes make them considered to be one of the most promising cathode materials in sodium-ion batteries. However, layered oxides also have disadvantages, such as being sensitive to moisture and carbon dioxide in the air, and being prone to chemical reactions, which affect the structural stability and electrochemical properties of the material, while increasing the cost of synthesis, processing and transportation of the material.

[0004] Therefore, the industry is in urgent need of a new technology for sodium ion positive electrode materials and their preparation methods. Summary of the invention

[0005] In view of the problem that the layered metal oxide positive electrode of the sodium ion battery in the prior art is unstable in the air, the present invention uses a phosphoric acid self-assembled monolayer to coat the surface of the sodium ion layered oxide material at the nanometer level. Through the action between the phosphonic acid head group and the hydroxyl group on the surface of the oxide material, the phosphonic acid molecules can be connected on the surface of the layered oxide through strong chemical bonds to form an ordered monolayer, which can directly prevent water molecules from directly contacting the surface of the material, effectively inhibit the degradation reaction between the layered oxide material and the ambient air, and significantly improve the chemical stability of the layered oxide material in the ambient air, thereby maintaining its electrochemical performance.

[0006] To achieve the above object, the technical solution of the present invention is:

[0007] In a first aspect, the present invention provides a sodium ion positive electrode material, the sodium ion positive electrode material comprising a layered oxide matrix Nax M y N z T i O n , and phosphonic acid molecules coated on the surface of the layered oxide matrix;

[0008] The mass of the phosphonic acid molecules accounts for 1-5% of the mass of the layered oxide matrix Na x M y N z T i O n ;

[0009] Among them, M, N, and T are different kinds of metal elements, and the M, N, and T metal elements are selected from one or more of Ni, Fe, Mn, Li, Ca, Al, Mg, Zr, Nb, Ta, Ti, Sn, Co, and Cu; 0.66 ≤ x < 1.1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ i ≤ 1, y + z + i = 1, 1.85 < n < 2.15; the values of x, y, z, i, and n satisfy the charge balance of the chemical formula.

[0010] It should be understood that, without special instructions, x, y, z, i, etc. in the context of the present invention represent the relative proportions of the amounts of substances of each element in the layered oxide sodium ion cathode material. For example, when x = 1, y = 1 / 3, z = 1 / 3, i = 1 / 3, and n = 2, the molecular formula of the layered oxide matrix is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0011] Preferably, the thickness of the phosphonic acid molecule coating layer in the sodium ion cathode material is 2-10 nm.

[0012] Preferably, the D50 of the sodium ion cathode material is 1-3 μm.

[0013] Preferably, the sodium ion cathode material is electrically neutral.

[0014] In a second aspect, the present invention also provides a method for preparing the above sodium ion cathode material, comprising the following steps:

[0015] (1) Mix the sodium source, metal source compound, and complexing agent in accordance with stoichiometric numbers and dissolve them fully to obtain a clear and transparent solution, then evaporate the solvent to obtain a gel, and finally dry it to obtain a precursor;

[0016] (2) Grind the precursor obtained in step (1) into a powder, then perform two sinterings, and after cooling, perform crushing, grinding, and sieving in sequence to obtain the layered oxide matrix;

[0017] (3) dispersing the phosphonic acid molecules in a solvent and stirring until fully dissolved;

[0018] (4) adding the layered oxide matrix to the solution obtained in step (3), fully dispersing the layered oxide matrix in the solution and stirring the solution for reaction;

[0019] (5) After the stirring reaction is completed, centrifugation is performed, and the precipitate is washed and dried to obtain the sodium ion positive electrode material.

[0020] Preferably, the sodium source in step (1) includes any one or more of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate, and sodium nitrate; the metal source compound includes any one or more of metal nitrate, metal sulfate, metal acetate, and metal chloride; and the complexing agent includes any one or more of citric acid, ethylenediaminetetraacetic acid, and ethylene glycol.

[0021] Preferably, the drying temperature in step (1) is 125-150°C; in step (2), the first sintering temperature of the two sinterings is 500-600°C for 4-6 hours, and the second sintering temperature is 850-1000°C for 10-15 hours.

[0022] Preferably, the phosphonic acid molecules in step (3) include any one or more of decylphosphonic acid, undecylphosphonic acid, dodecylphosphonic acid, hexadecylphosphonic acid, octadecylphosphonic acid, dihexadecylphosphonic acid, and dioctadecylphosphonic acid; and the solvent includes any one or more of ethanol, tetrahydrofuran, toluene, and N-methylpyrrolidone.

[0023] Preferably, the amount of the phosphonic acid molecules used in step (3) is 1-5% of the mass of the layered oxide matrix.

[0024] Preferably, the stirring reaction time in step (4) is 2-10 hours, the temperature is 30-45°C, and the humidity condition is a dew point temperature of -50 to -40°C; the centrifugal speed in step (5) is 5000-10000 rpm, and the time is 10-20 minutes.

[0025] In a third aspect, the present invention further provides a sodium ion battery positive electrode, comprising: the sodium ion positive electrode material, adhesive, and conductive additive described in the first aspect are mixed into a slurry by a solvent, coated on the surface of a current collector, and dried to form the sodium ion battery positive electrode.

[0026] Preferably, the conductive additive is one or more of carbon nanotubes, acetylene black, conductive carbon black, conductive graphite, carbon fiber, and graphene; the proportion of the conductive agent to the positive electrode of the sodium ion battery is less than or equal to 20wt%; the adhesive is one or more of polyolefins, fluorine-containing resins, polypropylene resins, and rubbers; the proportion of the adhesive to the positive electrode of the sodium ion battery is less than or equal to 10wt%; and the solvent is N-methylpyrrolidone.

[0027] More preferably, the positive electrode comprises the following components in parts by weight: 80 wt % of the sodium ion positive electrode material, 10 wt % of conductive carbon black, and 10 wt % of polyvinylidene fluoride.

[0028] The present invention has the following beneficial effects:

[0029] 1. The present invention provides a sodium ion positive electrode material and a preparation method thereof, wherein the sodium ion positive electrode material comprises a layered oxide Na x M y N z T i O n , and phosphonic acid molecules coated on the surface of the layered oxide; the mass of the phosphonic acid molecules accounts for 1.3% of the layered oxide matrix Na x M y N z T i O n1-5% of the mass; wherein, M, N, and T are different types of metal elements and are selected from one or more of Ni, Fe, Mn, Li, Ca, Al, Mg, Zr, Nb, Ta, Ti, Sn, Co, and Cu; 0.66 ≤ x < 1.1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ i ≤ 1, y + z + i = 1, 1.85 < n < 2.15; the values of x, y, z, i, and n satisfy the charge balance of the chemical formula. A preparation method of a sodium ion cathode material provided by the present invention adopts a one-step liquid phase synthesis method. By simply mechanically stirring and mixing a layered oxide matrix with an organic phosphoric acid molecular solution, strong chemical bonding between molecules and the layered oxide matrix can be achieved. When the phosphonic acid molecules contact the oxide surface, the hydroxyl groups of the phosphonic acid groups will interact with the hydroxyl groups on the surface of the layered oxide matrix, and covalent bonds are formed through a condensation reaction. Through the multidentate coordination between the phosphoric acid molecules and the surface of the layered oxide matrix, the surface of the layered oxide material particles is spontaneously and uniformly coated. The present invention forms a thin and dense nanoscale hydrophobic coating layer on the surface of the layered oxide material through a simple and low-cost process, reduces the influence of the coating layer on the electrochemical performance of the layered oxide material. At the same time, the uniform hydrophobic coating layer can avoid direct contact between the surface of the layered oxide material particles and water molecules in the air, inhibit side reactions brought by water and carbon dioxide, prevent the loss of active Na in the material, and effectively solve the problems of poor stability of the material in the air, crystal structure change, and significant reduction in electrochemical performance.

[0030] 2. A sodium ion cathode material provided by the present invention controls parameters such as solvent type, reaction time, and temperature to regulate the binding strength of phosphonic acid molecules, the molecular coating amount, and the orderliness of the coating layer, avoiding problems such as the loss of active sodium on the surface of the layered oxide material caused by excessive coating and the resulting reduction in reversible capacity; at the same time, the synthesis and preparation process of the present invention is simple and low-cost. During the subsequent material processing of the layered oxide, there is no need to create a harsh drying environment, greatly reducing the production and preparation cost, and being suitable for large-scale industrial production.

[0031] In addition to the purposes, features, and advantages described above, the present invention has other purposes, features, and advantages. The following will refer to the drawings for a further detailed description of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0033] Figure 1 XRD pattern of the sodium ion cathode material prepared in Example 1;

[0034] Figure 2 is a SEM image of the sodium ion positive electrode material prepared in Example 1;

[0035] Figure 3 is a TEM image of the layered oxide substrate material prepared in Comparative Example 1;

[0036] Figure 4 is a TEM image of the sodium ion positive electrode material prepared in Example 1;

[0037] Figure 5 is the XRD pattern of the sodium ion positive electrode material prepared in Example 1 after aging for 7 days;

[0038] Figure 6 is the XRD pattern of the layered oxide material prepared in Comparative Example 1 after aging for 7 days;

[0039] Figure 7 is the charge and discharge curve of the first cycle of the battery finally assembled from the sodium ion positive electrode material prepared in Example 1 at 0.1C;

[0040] Figure 8 This is the charge and discharge curve of the first cycle of the battery finally assembled from the layered oxide material prepared in Comparative Example 1 at 0.1C;

[0041] Fig. 9 The first cycle charge and discharge curve of the battery finally assembled after the sodium ion positive electrode material prepared in Example 1 was aged for 7 days at 0.1C;

[0042] Fig.10 This is the charge and discharge curve of the first cycle at 0.1C of the battery finally assembled after aging the layered oxide material prepared in Comparative Example 1 for 7 days. DETAILED DESCRIPTION

[0043] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, but the present invention can be implemented in many different ways as defined and covered by the claims.

[0044] Example 1

[0045] A sodium ion positive electrode material, the preparation method of which comprises the following steps:

[0046] (1) Sodium acetate, ferric nitrate, nickel acetate, and manganese acetate were fully mixed and dissolved in 50 mL of deionized water according to a stoichiometric ratio of 1.05:1 / 3:1 / 3:1 / 3, and then mixed with 50 mL of citric acid aqueous solution under vigorous stirring to obtain a clear solution. The obtained solution was heated and stirred in a 90°C oil bath, and the excess aqueous solution was evaporated until a transparent viscous gel was formed. The formed gel was dried at 125°C overnight to obtain a precursor.

[0047] (2) The precursor is ground into powder and placed in a muffle furnace. After sintering at 500°C for 6 hours, it is ground again and pressed into tablets. It is further sintered at 900°C for 12 hours. After cooling, a sintered product is obtained. The sintered product is then crushed, ground, and sieved in sequence to obtain a layered oxide matrix with a molecular formula of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0048] (3) dispersing dihexadecylphosphonic acid in tetrahydrofuran solution and stirring until fully dissolved;

[0049] (4) Add the layered oxide matrix, fully disperse it in the solution, and stir the reaction at a temperature of 35°C and a dew point of -40°C for 8 hours; the mass of dihexadecylphosphonic acid is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 3% of the mass of O2.

[0050] (5) After the stirring reaction is completed, the mixture is centrifuged at 8000 rpm for 20 min, and the precipitate is washed and dried to obtain the sodium ion positive electrode material.

[0051] Example 2

[0052] A sodium ion positive electrode material, the preparation method of which comprises the following steps:

[0053] (1) Sodium acetate, magnesium acetate, nickel acetate, and manganese acetate were fully mixed and dissolved in 50 mL of deionized water according to a stoichiometric ratio of 1.05:0.1:0.5:0.4, and then mixed with 50 mL of citric acid aqueous solution under vigorous stirring to obtain a clear solution. The obtained solution was heated and stirred in a 90° C. oil bath, and the excess aqueous solution was evaporated until a transparent viscous gel was formed. The formed gel was dried at 140° C. overnight to obtain a precursor.

[0054] (2) The precursor is ground into powder and placed in a muffle furnace. After sintering at 600°C for 4 hours, it is ground again and pressed into tablets. It is further sintered at 850°C for 15 hours. After cooling, a sintered product is obtained. The sintered product is then crushed, ground, and sieved in sequence to obtain a layered oxide matrix with a molecular formula of NaNi 0.5 Mn 0.4 Mg 0.1 O2.

[0055] (3) dispersing hexadecylphosphonic acid in tetrahydrofuran solution and stirring until fully dissolved;

[0056] (4) Add the layered oxide matrix, fully disperse it in the solution, and stir the reaction for 10 hours at a temperature of 30°C and a dew point temperature of -40°C; the mass of dihexadecylphosphonic acid is NaNi0.5 Mn 0.4 Mg 0.1 1% of O2 mass.

[0057] (5) After the stirring reaction is completed, the mixture is centrifuged at 5000 rpm for 20 min, and the precipitate is washed and dried to obtain the sodium ion positive electrode material.

[0058] Example 3

[0059] A sodium ion positive electrode material, the preparation method of which comprises the following steps:

[0060] (1) Sodium acetate, ferric nitrate, nickel acetate, and manganese acetate were fully mixed and dissolved in 50 mL of deionized water according to a stoichiometric ratio of 1.05:1 / 3:1 / 3:1 / 3, and then mixed with 50 mL of citric acid aqueous solution under vigorous stirring to obtain a clear solution. The obtained solution was heated and stirred in a 90°C oil bath, and the excess aqueous solution was evaporated until a transparent viscous gel was formed. The formed gel was dried at 145°C overnight to obtain a precursor.

[0061] (2) The precursor is ground into powder and placed in a muffle furnace. After sintering at 550°C for 5 hours, it is ground again and pressed into tablets. It is further sintered at 1000°C for 10 hours. After cooling, a sintered product is obtained. The sintered product is then crushed, ground, and sieved in sequence to obtain a layered oxide matrix with a molecular formula of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2;

[0062] (3) dispersing undecylphosphonic acid in an ethanol solution and stirring until fully dissolved;

[0063] (4) adding the layered oxide matrix, fully dispersing it in the solution, and stirring the reaction at a temperature of 40°C and a dew point of -45°C for 6 hours; wherein the mass of undecylphosphonic acid is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 5% of O2 mass.

[0064] (5) After the stirring reaction is completed, the mixture is centrifuged at 10000 rpm for 10 min, and the precipitate is washed and dried to obtain the sodium ion positive electrode material.

[0065] Example 4

[0066] A sodium ion positive electrode material, the preparation method of which comprises the following steps:

[0067] (1) Sodium acetate, ferric nitrate, nickel acetate, and manganese acetate were fully mixed and dissolved in 50 mL of deionized water according to a stoichiometric ratio of 1.05:1 / 3:1 / 3:1 / 3, and then mixed with 50 mL of citric acid aqueous solution under vigorous stirring to obtain a clear solution. The obtained solution was heated and stirred in a 90°C oil bath, and the excess aqueous solution was evaporated until a transparent viscous gel was formed. The formed gel was dried at 150°C overnight to obtain a precursor.

[0068] (2) The precursor is ground into powder and placed in a muffle furnace. After sintering at 500°C for 6 hours, it is ground again and pressed into tablets. It is further sintered at 900°C for 12 hours. After cooling, a sintered product is obtained. The sintered product is then crushed, ground, and sieved in sequence to obtain a layered oxide matrix with a molecular formula of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2;

[0069] (3) dispersing dodecylphosphonic acid in tetrahydrofuran solution and stirring until fully dissolved;

[0070] (4) Add the layered oxide matrix, fully disperse it in the solution, and stir the reaction for 2 hours at a temperature of 45°C and a dew point temperature of -50°C; the mass of dodecylphosphonic acid is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 3% of the mass of O2.

[0071] (5) After the stirring reaction is completed, the mixture is centrifuged at 8000 rpm for 15 min, and the precipitate is washed and dried to obtain the sodium ion positive electrode material.

[0072] Comparative Example 1 (no phosphonic acid molecules added, only layered oxide)

[0073] A sodium ion positive electrode material, the preparation method of which comprises the following steps:

[0074] (1) Sodium acetate, ferric nitrate, nickel acetate, and manganese acetate were fully mixed and dissolved in 50 mL of deionized water according to a stoichiometric ratio of 1.05:1 / 3:1 / 3:1 / 3, and then mixed with 50 mL of citric acid aqueous solution under vigorous stirring to obtain a clear solution. The obtained solution was heated and stirred in a 90°C oil bath, and the excess aqueous solution was evaporated until a transparent viscous gel was formed. The formed gel was dried at 125°C overnight to obtain a precursor.

[0075] (2) The precursor is ground into powder and placed in a muffle furnace. After sintering at 500°C for 6 hours, it is ground again and pressed into tablets. It is further sintered at 900°C for 12 hours. After cooling, a sintered product is obtained. The sintered product is then crushed, ground, and sieved in sequence to obtain a layered oxide matrix with a molecular formula of NaNi1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is the sodium ion positive electrode material.

[0076] Comparative Example 2 (phosphonic acid molecules are short-chain small molecules)

[0077] The difference between Comparative Example 2 and Example 1 is that in step (3), ethylphosphonic acid is used instead of dihexadecylphosphonic acid, and the other steps are the same as those in Example 1.

[0078] Comparative Example 3 (the solvent for dissolving the phosphonic acid molecules is methanol)

[0079] The difference between Comparative Example 3 and Example 1 is that in step (3), dihexadecylphosphonic acid is dispersed in a methanol solution instead of in a tetrahydrofuran solution, and the other steps are the same as in Example 1.

[0080] Comparative Example 4 (phosphonic acid molecule concentration is too low)

[0081] The difference between Comparative Example 4 and Example 1 is that in step (4), the mass of dihexadecylphosphonic acid is NaNi 1 / 3 Fe 1 / 3Mn 1 / 3 The amount of O2 is 0.5% by mass, and the other steps are the same as those in Example 1.

[0082] Comparative Example 5 (phosphonic acid molecule concentration is too high)

[0083] The difference between Comparative Example 5 and Example 1 is that in step (4), the mass of dihexadecylphosphonic acid is NaNi 1 / 3 Fe 1 / 3Mn 1 / 3 The amount of O2 is 6% by mass, and the other steps are the same as those in Example 1.

[0084] Comparative Example 6 (reaction temperature is too low)

[0085] The difference between Comparative Example 6 and Example 1 is that in step (4), the reaction temperature is 25°C, and the other steps are the same as Example 1.

[0086] Comparative Example 7 (reaction temperature is too high)

[0087] The difference between Comparative Example 7 and Example 1 is that in step (4), the reaction temperature is 50° C., and the other steps are the same as Example 1.

[0088] Figure 1 is the XRD pattern of the sodium ion positive electrode material prepared in Example 1. Figure 1 It can be seen that the sodium ion positive electrode material prepared in Example 1 is a hexagonal α-NaFeO2 layered structure (space group: R-3m), which is consistent with the standard PDF card structure (PDF#54-0887); Figure 2 This is a SEM image of the sodium ion positive electrode material prepared in Example 1. The surface of the material is smooth and flat, indicating that the coating of phosphonic acid molecules has no obvious effect on the morphology of the layered oxide material; Figure 3 This is a TEM image of the layered oxide substrate material prepared in Comparative Example 1, and the surface of the material is smooth; Figure 4 This is a TEM image of the sodium ion positive electrode material prepared in Example 1. It can be seen that a thin layer of phosphonic acid molecules uniformly covers the surface of the layered oxide material.

[0089] According to the conventional method in the art, the sodium ion positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-7 were subjected to aging tests under constant temperature and humidity conditions, and then the corresponding materials were used to prepare positive electrode sheets, and the prepared positive electrode sheets, sodium sheets, electrolytes and diaphragms were assembled into CR2032 button batteries in a glove box filled with argon.

[0090] Figure 5 is the XRD pattern of the sodium ion positive electrode material prepared in Example 1 after aging for 7 days. It can be seen that compared with the initial state of the material ( Figure 1 ), there is no obvious crystal structure change after aging for 7 days. Figure 6 This is the XRD diagram of the layered oxide material prepared in Example 1 after aging for 7 days. Impurity diffraction peaks are obviously generated at the positions of 32°, 33°, and 38°, indicating that the crystal structure of the material has undergone significant changes.

[0091] The sodium ion positive electrode material, adhesive, and conductive additive prepared in Examples 1-4 and Comparative Examples 1-7 are mixed into a slurry with a solvent, coated on the surface of the current collector, and dried to form a sodium ion battery positive electrode sheet. The prepared positive electrode material includes the following components in parts by weight: 80wt% of the sodium ion positive electrode material, 10wt% of conductive carbon black, and 10wt% of polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.

[0092] The prepared positive electrode sheet, sodium sheet, electrolyte and diaphragm were assembled into a CR2032 button battery in a glove box filled with argon. The solvent of the electrolyte was composed of ethylene carbonate and propylene carbonate, with a volume ratio of 1:1. The solute of the electrolyte was 1M NaClO4, and the diaphragm was Whatman glass fiber. The prepared button battery was tested for electrochemical performance (first week charging capacity (mAh / g)). The results are as follows: Figure 7-10 And as shown in Table 1.

[0093] Figure 7 This is the charge and discharge curve of the first cycle of the battery finally assembled from the sodium ion positive electrode material prepared in Example 1 at 0.1C, and the material discharge specific capacity is 131.4 mAh / g. Figure 8This is the charge and discharge curve of the first cycle of the battery finally assembled from the layered oxide material prepared in Comparative Example 1 at 0.1C, and the material discharge specific capacity is 136.9 mAh / g. Due to the combination of the head group of the phosphonic acid molecule with some active sodium ions on the surface of the material, the capacity of the coated material is slightly reduced compared to the uncoated material, but the difference is not large. Fig. 9 This is the charge and discharge curve of the first cycle of the battery assembled after aging the sodium ion positive electrode material prepared in Example 1 for 7 days at 0.1C. The material discharge specific capacity is 117.6 mAh / g. Fig.10 This is the charge and discharge curve of the first cycle of the battery assembled from the layered oxide material prepared in Comparative Example 1 after aging for 7 days at 0.1C. The material discharge capacity is 48.7 mAh / g. Compared with Comparative Example 1, the capacity retention rate of Example 1 of the present invention after aging for 7 days is very good, while the discharge capacity of the material in Comparative Example 1 that is not coated with phosphonic acid decreases sharply. Figure 7-10 It can be seen that when the sodium ion positive electrode material prepared by the method of the present invention is exposed to the air, the loss of active Na in the material can be greatly prevented. Therefore, after aging for 7 days, the capacity retention rate is significantly improved compared with the uncoated material, and the coated material exhibits good air stability. The various properties of Examples 2-4 are similar to those of Example 1 and will not be repeated here.

[0094] Table 1 Electrochemical properties of button cells prepared in Example 1 and Comparative Examples 1-7

[0095]

[0096]

[0097] As shown in Table 1, compared with Comparative Example 1, the sodium ion positive electrode material prepared by Example 1 of the present invention has significantly reduced capacity decay after aging for 7 days, indicating that the phosphonic acid molecule coating can significantly improve the air stability of the layered oxide material, and can maintain the electrochemical performance well after exposure under constant temperature and humidity conditions. Compared with Example 1, Comparative Example 2 shows that the material coated with short-chain alkyl molecules has a large capacity loss after the aging experiment, indicating that the hydrophobic molecules have limited effect on improving the air stability of the material; Comparative Example 3 shows that when methanol is used as a solvent, the protective effect of the dihexadecyl phosphoric acid molecule on the material is reduced, because the solubility of long-chain molecules in methanol is limited, and methanol has a strong polarity, which will affect the uniformity and density of the phosphonic acid molecule layer; Comparative Examples 4 and 6 show that when the molecular concentration is low and the reaction temperature is low, the coating of the material will be insufficient, which will also affect the improvement of the air stability of the phosphonic acid molecule; Comparative Examples 5 and 7 show that the molecular concentration is high and the reaction temperature is high, which will lead to excessive coating of the material, which will affect the ion diffusion, so that the electrochemical performance of the coated material is significantly reduced. It can be seen from the conclusion of the above comparative example that the reaction parameters need to be reasonably regulated in order to obtain a thin, uniform and dense hydrophobic phosphonic acid molecular layer.

[0098] In summary, the preparation method of a sodium ion positive electrode material provided by the present invention adopts a one-step liquid phase synthesis method, and a strong chemical bond between the molecule and the layered oxide matrix can be achieved by simply mechanically stirring and mixing the layered oxide matrix with the organic phosphoric acid molecule solution. When the phosphonic acid molecule contacts the oxide surface, the hydroxyl group of the phosphonic acid group interacts with the hydroxyl group on the surface of the layered oxide matrix, and forms a covalent bond through a condensation reaction. Through the multi-dentate coordination between the phosphoric acid molecule and the surface of the layered oxide matrix, the surface of the layered oxide material particle is spontaneously and uniformly coated. The present invention forms a thin and dense nanoscale hydrophobic coating layer on the surface of the layered oxide material through a simple process and low-cost method, reducing the influence of the coating layer on the electrochemical properties of the layered oxide material. At the same time, the uniform hydrophobic coating layer can avoid the direct contact between the surface of the layered oxide material particle and the water molecules in the air, inhibiting the side reactions caused by water and carbon dioxide, and preventing the loss of active Na in the material, effectively solving the problem of poor stability of the material in the air, changes in crystal structure and significant reduction in electrochemical performance.

[0099] In addition, the present invention regulates the binding strength of the phosphonic acid molecules, the molecular coating amount, and the orderliness of the coating layer by controlling parameters such as the solvent type, reaction time, and temperature, thereby avoiding the loss of active sodium on the surface of the layered oxide material due to excessive coating and the resulting reduction in reversible capacity. At the same time, the present invention has a simple synthesis and preparation process with low cost. In the subsequent material processing of the layered oxide, there is no need to create a strict drying environment, which greatly reduces the production and preparation cost and is suitable for large-scale industrial production.

[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A sodium ion positive electrode material, characterized in that: The sodium ion positive electrode material comprises a layered oxide matrix Na x M y N z T i O n , and phosphonic acid molecules coated on the surface of the layered oxide matrix; The mass of the phosphonic acid molecules accounts for 1.3% of the layered oxide matrix Na x M y N z T i O n 1-5% of mass; Among them, M, N, and T are different types of metal elements, and the metal elements M, N, and T are selected from one or more of Ni, Fe, Mn, Li, Ca, Al, Mg, Zr, Nb, Ta, Ti, Sn, Co, and Cu; 0.66 ≤ x < 1.1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ i ≤ 1, y + z + i = 1, 1.85 < n < 2.15; the values of x, y, z, i, and n satisfy the charge balance of the chemical formula.

2. A sodium ion positive electrode material according to claim 1, characterized in that: The thickness of the phosphonic acid molecule coating layer in the sodium ion cathode material is 2 - 10 nm.

3. A sodium ion positive electrode material according to claim 1, characterized in that: The D50 of the sodium ion cathode material is 1 - 3 μm.

4. A method for preparing a sodium ion positive electrode material according to any one of claims 1 to 3, characterized in that: It includes the following steps: (1) Mix the sodium source, metal source compound, and complexing agent in stoichiometric amounts and dissolve them fully to obtain a clear and transparent solution, then evaporate the solvent to obtain a gel, and finally dry it to obtain a precursor; (2) Grind the precursor prepared in step (1) into a powder, perform two sinterings, and after cooling, perform crushing, grinding, and sieving in sequence to obtain a layered oxide matrix; (3) Disperse the phosphonic acid molecules in a solvent and stir until fully dissolved; (4) Add the layered oxide matrix to the solution prepared in step (3), disperse it fully in the solution, and then carry out a stirring reaction; (5) After the stirring reaction ends, perform centrifugation, take the precipitate, wash and dry it to obtain the sodium ion cathode material.

5. The preparation method according to claim 4, characterized in that: In step (1), the sodium source includes any one or more of sodium carbonate, sodium hydroxide, sodium acetate, sodium oxalate, and sodium nitrate; the metal source compound includes any one or more of metal nitrates, metal sulfates, metal acetates, and metal chlorides; the complexing agent includes any one or more of citric acid, ethylenediaminetetraacetic acid, and ethylene glycol.

6. The preparation method according to claim 4, characterized in that: In step (1), the drying temperature is 125 - 150 °C; in step (2), for the two sinterings, the first sintering temperature is 500 - 600 °C, the time is 4 - 6 h, the second sintering temperature is 850 - 1000 °C, and the time is 10 - 15 h.

7. The preparation method according to claim 4, characterized in that: In step (3), the phosphonic acid molecules include any one or more of decylphosphonic acid, undecylphosphoric acid, dodecylphosphonic acid, hexadecylphosphonic acid, octadecylphosphonic acid, bis(hexadecyl)phosphonic acid, and bis(octadecyl)phosphoric acid; the solvent includes any one or more of ethanol, tetrahydrofuran, toluene, and N - methylpyrrolidone.

8. The preparation method according to claim 4, characterized in that: In step (3), the dosage of the phosphonic acid molecules is 1 - 5% of the mass of the layered oxide matrix.

9. The preparation method according to claim 4, characterized in that: In step (4), the time of the stirring reaction is 2 - 10 h, the temperature is 30 - 45 °C, and the humidity condition is a dew point temperature of -50 to -40 °C; in step (5), the rotation speed of the centrifugation is 5000 - 10000 rpm, and the time is 10 - 20 min.

10. A sodium ion battery positive electrode, characterized in that: The sodium ion battery cathode material according to any one of claims 1 - 3 or the sodium ion battery cathode material prepared by the preparation method according to any one of claims 4 - 9, a binder, and a conductive additive are made into a slurry with a solvent, coated on the surface of a current collector, and after drying, the sodium ion battery cathode is formed.

Citation Information

Cited By

  • Sodium ion layered oxide positive electrode material and preparation method thereof

    CN120784355A